(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Background: The rapid transition to online education has created significant challenges in supporting students’ emotional well-being, particularly for music education students who require emotional expression and collaborative engagement difficult to replicate in digital environments. Current one-size-fits-all interventions fail to address individual differences in emotional states and learning preferences.Purpose: This study investigates the effectiveness of a personalized meditation music recommendation system based on real-time emotion assessment in online music education, examining its impact on university students’ self-regulation capabilities and emotional well-being.Methods: A mixed-methods quasi-experimental design was employed with 72 undergraduate music majors over 8 weeks. Participants were randomly assigned to experimental (n=36) and control (n=36) groups. The experimental group received personalized music recommendations through a three-layer mapping system based on daily PANAS-SF assessments, while the control group accessed fixed meditation playlists.Results: The experimental group demonstrated significant improvements in emotion regulation (t=4.23, p<0.001), with self-regulation scores increasing from M=3.42 to M=4.56 (d=1.38). Qualitative analysis revealed themes of emotional validation, enhanced autonomy, and meta-cognitive awareness. 85% of participants reported improved learning focus, with voluntary engagement exceeding minimum requirements by 93%.Conclusion: Personalized meditation music recommendations based on emotion assessment effectively enhance self-regulation and emotional well-being in online music education contexts, offering an accessible, low-cost solution for institutional implementation.